USING A NEW DIGITAL TECHNIQUES TO BUILT, UPDATE AND ANALYSIS OF DATABASE OF A THEMATIC PAPER MAP CASE STUDY/ MAHALA 612 IN AL-YARMOUK / BAGHDAD/ IRAQ - Zakariya Jasim, Oday (Journal of Engineering and Sustainable Development, 2015)
The new digital technology in the field of maps and satellite images are one of the Important means in Build and update database of a thematic paper map, which is for the study of a particular subject in a specific time and that because of its these technologies from the full capability to deal with paper maps and turn it into a digital form which can be read co-ordinates digitally. From this point has become a set of these modern digital technologies necessary weapon used by the planner to control of data variables in a specific time and place specified. The inefficiency of paper maps through their inability to identify the logical relationships between the elements of the spatial maps does not appear effect on any element last linked with a logical, as well as the difference in scaling of these maps are disabled in the work of analysis and comparison mathematically and finally, the time that started to build the spatial and the attribute data is considered obstacle to update the map. Accordingly the updating of the data of the thematic map are the process is very expensive and time-consuming and therefore the lack of planning and engineering trend to overcome those obstacles are the problem of the research, . This approach can be summed up the adoption of satellite imagery techniques with high resolution of one meter and digital image processing software and GIS programs as well as the technique of the Global Positioning System.